Governance: Analisis Perubahan Pemerintahan - Mukrimin, Mukrimin (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
Scholars have viewed governance as a form of government reform. The broad concept of governance has recently come to encompass governance reform. Governments have since undermined the meaning of transition. The term governance has become a trendy term for reforming the public sector. Governance is concerned with issues of public administration and policy. This article argues that governments intend to maintain political and hierarchical structures while establishing merit recruitment and promotion systems. The purpose of governance is mainly to help accelerate the functioning of the public sector. Using Rod Rhodes' notion of governance, this study finds that political authority tends to be delegated power to acid. Institutional separation and pluralization have significantly weakened the central government's ability to direct. Although there is no agreement on the implications of change, governance emerged because of government reform. This study shows that governance in the changing understanding and practice of governance mechanisms has more to do with the direction and arrangement of public affairs whose purpose is to improve, organize, and unravel all human affairs.